Ink composition, and laminate having ink layer
A laminate with heat-shrinkable polyolefin films and printing layers using a specific resin combination in the ink composition addresses issues of pigment dispersion and physical properties, achieving improved adhesion and resistance.
Patent Information
- Application Number
- JP2024027476
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-02-27
- Publication Date
- 2025-09-08
AI Technical Summary
Existing laminates with heat-shrinkable polyolefin films and printing layers, particularly those using urethane resin in the printing layer, fail to achieve satisfactory results in terms of pigment dispersion and physical properties such as adhesion, scratch resistance, rubbing resistance, blocking resistance, and heat resistance.
Incorporating a combination of soluble nitrocellulose resin, polyamide resin, and ketone resin as binder resins in an ink composition, along with specific organic solvents and optional additives like wax and silica, to form an ink layer in a laminate structure.
The laminate exhibits well-balanced and favorable results in all evaluation items, including pigment dispersibility and various physical properties of overprinted ink prints, such as adhesion, scratch resistance, crumple resistance, and blocking resistance.
Smart Images

Figure 2025130353000001 
Figure 2025130353000002 
Figure 2025130353000003
Abstract
Description
[Technical Field]
[0001] The present invention relates to an ink composition and a laminate having an ink layer. [Background technology]
[0002] Overwrap film is a type of packaging material that is attached to various adherends, such as containers containing food or daily necessities, by heat shrinking. For example, many cup containers containing instant noodles are wrapped and packaged with an overlap film provided with a design print layer such as a picture, trademark, product description, etc. Incidentally, an overlap film using a heat-shrinkable polyolefin film is known. If a polyolefin film is corona discharge treated, problems can arise during post-processing, such as when the film is sealed and packaged using a fusing heater, as the corona discharge treatment can cause the sealed area to peel off, making packaging difficult. For this reason, it is necessary to print without corona discharge treatment, and if corona discharge treatment is not performed, a possible configuration is to provide an anchor coat layer between the heat-shrinkable polyolefin film and the design print layer to improve adhesion between the polyolefin film and the design print layer. For example, an overlap film has been proposed that has a heat-shrinkable polyolefin film, an anchor coat layer laminated adjacent to the heat-shrinkable polyolefin film, and a design print layer laminated adjacent to the anchor coat layer (see, for example, Patent Document 1). In Patent Document 1, a urethane resin is contained in a design print layer provided on an anchor coat layer and in a second print layer provided further thereon. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Japanese Patent Application Laid-Open No. 2016-141403 Summary of the Invention [Problem to be solved by the invention]
[0004] The present inventors have investigated an overlap film having a heat-shrinkable polyolefin film, an anchor coat layer, and a printing layer (ink layer) as shown in Patent Document 1 above. As a result, it was found that in laminates having a heat-shrinkable polyolefin film and a printing layer (ink layer) (particularly laminates having a heat-shrinkable polyolefin film, an anchor coat layer, and a printing layer (ink layer)), if a urethane resin is used in the printing layer (ink layer), satisfactory results may not be obtained in terms of pigment dispersion and the physical properties of the overprinted ink print (e.g., adhesion, scratch resistance, rubbing resistance, blocking resistance, heat resistance, etc.). Pigment dispersion is a critical process in the production of paints and inks, and its quality affects the product's optical properties, such as gloss, tinting strength, and hiding power, as well as rheological properties, such as viscosity, fluidity, leveling, and flow, and stability over time, such as sedimentation, aggregation, and the occurrence of particles. Therefore, improving pigment dispersibility is important in order to atomize and stabilize the pigment particles. The object of the present invention is to provide a laminate having a heat-shrinkable polyolefin film and a printing layer (ink layer) (particularly a laminate having a heat-shrinkable polyolefin film, an anchor coat layer, and a printing layer (ink layer)), which can show well-balanced and favorable results in all evaluation items, including pigment dispersibility and various physical properties of overprinted ink prints (adhesion, scratch resistance, crumple resistance, blocking resistance, heat resistance, etc.), and to provide an ink composition for forming the printing layer (ink layer) that constitutes said laminate. [Means for solving the problem]
[0005] As a result of intensive research into solving the above-mentioned problems, the present inventors have found that by incorporating a combination of specific resins as binder resins that constitute an ink composition, a laminate (e.g., an overlap film) having an ink layer formed from an ink composition containing the binder resins can solve the above-mentioned problems of the present invention, and have thus completed the present invention.
[0006] That is, the present invention includes the following aspects. [1] A binder resin and an organic solvent are contained, The ink composition, wherein the binder resin contains soluble nitrocellulose resin, polyamide resin, and ketone resin. [2] The ink composition according to [1], wherein the soluble nitrocellulose resin and the polyamide resin are contained in an amount of 60 mass% or more in terms of solid content relative to the total amount of the binder resin. [3] The ink composition according to [1] or [2], wherein the organic solvent contains at least one of an aliphatic hydrocarbon solvent, an ester solvent, an alcohol solvent, and a glycol ether solvent. [4] The ink composition according to any one of [1] to [3], further comprising at least one of wax and silica. [5] The ink composition according to any one of [1] to [4], which is used to form an ink layer in a laminate having a heat-shrinkable film and an ink layer. [6] A laminate comprising a heat-shrinkable film, an anchor coat layer, and an ink layer laminated in this order, The ink layer is a layer formed using the ink composition according to any one of [1] to [5]. [7] The laminate according to [6], wherein the heat-shrinkable film is a polyolefin film. [8] A laminate comprising a heat-shrinkable film, an anchor coat layer, and an ink layer laminated in this order, The laminate according to [6], wherein the ink layer is composed of two or more ink layers, and at least one of the two or more ink layers that is in contact with the anchor coat layer is a layer formed using the ink composition according to any one of [1] to [5]. [9] A laminate comprising a heat-shrinkable film, an anchor coat layer, and an ink layer laminated in this order, The laminate according to [6], wherein the ink layer comprises two or more ink layers, and each of the two or more ink layers is formed using the ink composition according to any one of [1] to [5].
[10] The laminate according to [6], wherein the anchor coat layer-forming composition that forms the anchor coat layer contains at least a chlorinated polyolefin resin as a binder resin. [Effects of the Invention]
[0007] The present invention can provide a laminate having a heat-shrinkable polyolefin film and a printing layer (ink layer) (particularly a laminate having a heat-shrinkable polyolefin film, an anchor coat layer, and a printing layer (ink layer)), which can exhibit well-balanced and favorable results in all evaluation items, including pigment dispersibility and various physical properties of overprinted ink prints (adhesion, scratch resistance, crumple resistance, blocking resistance, heat resistance, etc.), and an ink composition for forming the printing layer (ink layer) that constitutes the laminate. DETAILED DESCRIPTION OF THE INVENTION
[0008] The present invention will be described in detail below. Note that the following explanation of the constituent elements is an example for explaining the present invention, and the present invention is not limited to these contents.
[0009] (Ink composition) The ink composition of the present invention is a composition used for forming an ink layer in a laminate having a heat-shrinkable polyolefin film and a printed layer (ink layer) (particularly a laminate having a heat-shrinkable polyolefin film, an anchor coat layer, and a printed layer (ink layer)). A detailed description of a "laminate" (eg, an overlap film) having a heat-shrinkable film, an ink layer, and an anchor coat layer disposed therebetween will be provided below. The ink composition of the present invention contains a binder resin and an organic solvent. The binder resin contains soluble nitrocellulose resin, polyamide resin, and ketone resin. In the present invention, by incorporating specific resins including soluble nitrocellulose resin, polyamide resin, and ketone resin into the ink composition, it is possible to produce a laminate that can show well-balanced results in all evaluation items, including pigment dispersibility and various physical properties of overprinted ink prints (adhesion, scratch resistance, crumpling resistance, blocking resistance, heat resistance, etc.), as shown in the examples below.
[0010] <Binder resin> The binder resin according to the present invention contains soluble nitrocellulose resin, polyamide resin, and ketone resin. The binder resin is contained in the ink composition in an amount of preferably 5.0 to 40.0 mass %, and more preferably 10.0 to 38.0 mass %.
[0011] <<Nitrified cotton resin>> The ink composition contains soluble nitrocellulose resin as a binder resin component. The soluble cellulose resin (nitrocellulose) is preferably obtained by reacting natural cellulose with nitric acid to replace three hydroxyl groups in the six-membered ring of the anhydroglucopyranose group in the natural cellulose with nitric acid groups to form a nitric acid ester. The molecular weight of the soluble cellulose resin is preferably a weight-average molecular weight of 5,000 to 200,000, more preferably 10,000 to 50,000. The glass transition temperature is preferably 120°C to 180°C. The soluble cellulose resin preferably has a nitrogen content of 10 to 13% by mass and an average degree of polymerization of 30 to 500, more preferably a nitrogen content of 10 to 13% by mass and an average degree of polymerization of 45 to 290. By including the soluble nitrocellulose resin, the scratch resistance, heat resistance and blocking resistance of the laminate can be improved.
[0012] <<Polyamide resin>> The polyamide resin is, for example, a thermoplastic polyamide soluble in an organic solvent, obtainable by polycondensation of a polybasic acid and a polyamine. In particular, a polyamide resin containing a reaction product of an acid component containing a polymerized fatty acid and / or a dimer acid with an aliphatic and / or aromatic polyamine is preferred, and one containing a portion of primary and secondary monoamines is even more preferred. Polybasic acids used as raw materials for polyamide resins include, but are not limited to, adipic acid, sebacic acid, azelaic acid, phthalic anhydride, isophthalic acid, suberic acid, glutaric acid, fumaric acid, pimelic acid, oxalic acid, malonic acid, succinic acid, maleic acid, terephthalic acid, 1,4-cyclohexyldicarboxylic acid, trimellitic acid, dimer acid, hydrogenated dimer acid, and polymerized fatty acid. Among these, polyamide resins containing a structure derived from dimer acid or polymerized fatty acid as the main component (50% by weight or more in the polyamide resin) are preferred. Here, polymerized fatty acid is obtained by, for example, the cyclization reaction of unsaturated fatty acid, and includes monobasic fatty acid, dimerized polymerized fatty acid (dimer acid), trimerized polymerized fatty acid, and the like. Fatty acids constituting dimer acid or polymerized fatty acid include those derived from natural oils such as soybean oil, palm oil, and rice bran oil, with those derived from oleic acid and linoleic acid being preferred. The polybasic acid may be used in combination with a monocarboxylic acid, such as acetic acid, propionic acid, lauric acid, palmitic acid, benzoic acid, or cyclohexanecarboxylic acid. Examples of polyamines include polyamines and primary or secondary monoamines. Examples of polyamines used in polyamide resins include aliphatic diamines such as ethylenediamine, propylenediamine, hexamethylenediamine, and methylaminopropylamine, and aliphatic polyamines such as diethylenetriamine and triethylenetetramine. Examples of alicyclic polyamines include cyclohexylenediamine and isophoronediamine. Examples of aromatic aliphatic polyamines include xylylenediamine, and examples of aromatic polyamines include phenylenediamine and diaminodiphenylmethane. Examples of primary and secondary monoamines include n-butylamine, octylamine, diethylamine, monoethanolamine, monopropanolamine, diethanolamine, and dipropanolamine. By including a polyamide resin, the adhesiveness and flexibility of the laminate can be improved.
[0013] <<Ketone resin>> Examples of the ketone resin of the present invention include condensates of methyl ethyl ketone, methyl isobutyl ketone, acetophenone, cyclohexanone and / or methylcyclohexanone with formaldehyde. As the ketone resin, for example, the Teg series manufactured by Evonik can be used. By including a ketone resin, it is possible to improve the pigment dispersibility in the ink layer and improve the scratch resistance and flexibility of the laminate.
[0014] The content of the soluble nitrocellulose resin in the ink composition is preferably 0.5 to 25.0 mass %, and more preferably 1.0 to 20.0 mass %. The polyamide resin is preferably contained in the ink composition in an amount of 2.0 to 20.0 mass %, more preferably 3.0 to 15.0 mass %. The ketone resin is contained in the ink composition in an amount of preferably 0.5 to 20.0 mass %, and more preferably 1.0 to 15.0 mass %. It is preferable that the ink composition contains 60 mass % or more of soluble nitrocellulose resin and polyamide resin in terms of solid content relative to the total amount of binder resin. The content ratio of the soluble nitrocellulose resin, polyamide resin, and ketone resin in the binder resin in the ink composition is preferably 10.0-55.0:30.0-60.0:10.0-30.0 in mass %.
[0015] <Organic solvents> The organic solvent according to the present invention is not particularly limited, but preferably contains at least one of an aliphatic hydrocarbon solvent, an ester solvent, an alcohol solvent, and a glycol ether solvent. The solvents can be used alone or in combination of two or more. For example, by using an alcohol-based solvent in addition to an ester-based solvent, deterioration of the flexographic plate during flexographic printing can be suppressed. Examples of organic solvents used in the present invention include aliphatic hydrocarbon organic solvents such as hexane, methylcyclohexane, heptane, octane, and decane; ester solvents such as methyl acetate, ethyl acetate, isopropyl acetate, normal propyl acetate, butyl acetate, amyl acetate, ethyl formate, and butyl propionate; alcohol solvents such as methanol, ethanol, propanol, butanol, and isopropyl alcohol; and glycol ether solvents such as ethylene glycol (mono- and di-)methyl ether, ethylene glycol (mono- and di-)ethyl ether, ethylene glycol monopropyl ether, ethylene glycol monoisopropyl ether, monobutyl ether, diethylene glycol (mono- and di-)methyl ether, diethylene glycol (mono- and di-)ethyl ether, diethylene glycol monoisopropyl ether, diethylene glycol monobutyl ether, triethylene glycol (mono- and di-)methyl ether, propylene glycol (mono- and di-)methyl ether, propylene glycol monopropyl ether, propylene glycol monobutyl ether, and dipropylene glycol (mono- and di-)methyl ether.
[0016] The organic solvent is contained in the ink composition in an amount of preferably 20.0 to 80.0 mass %, more preferably 25.0 to 75.0 mass %.
[0017] The ink composition of the present invention may further contain at least one of wax and silica.
[0018] <Wax> The ink composition may contain a wax. As the wax, for example, it is preferable to use polyolefin wax or fatty acid amide wax. Examples of polyolefin waxes include oxidized polyethylene wax and oxidized polypropylene wax. Examples of fatty acid amide waxes include saturated fatty acid amides such as stearic acid amide and palmitic acid amide, unsaturated fatty acid amides such as erucic acid amide, substituted amides, and aromatic amides.
[0019] The wax is contained in the ink composition in an amount of preferably 0.01 to 5.0 mass %, and more preferably 0.05 to 2.0 mass %. The content of silica in the ink composition is preferably 0.1 to 5.0 mass %, and more preferably 0.5 to 3.0 mass %.
[0020] <Ink layer> An ink layer is formed using the ink composition (solvent ink (an ink using an organic solvent, also referred to as solvent ink or oil-based ink in this specification)). The ink layer according to the present invention may be a single layer or may be formed from two or more layers. For example, the ink layer may be an ink layer consisting of two or more ink layers, including a design printed layer that displays various design displays such as a product name, a pattern, ingredient information, a barcode, a two-dimensional code, and a cautionary note, and a second printed layer that is colorless and transparent, colored and transparent, a single color without a pattern, or multiple colors without a pattern. The design print layer and the second print layer may be made up of a plurality of layers.
[0021] As described above, the design print layer is a print layer on which various design displays such as product names, pictures, ingredient labels, bar codes, two-dimensional codes, and warnings are displayed. The design print layer contains the binder resin and a colorant. As the colorant, a conventionally known pigment or dye can be used.
[0022] As described above, the second printed layer is a colorless and transparent, colored and transparent, a single-colored and patternless printed layer, or a multicolored and patternless printed layer. The second print layer contains the binder resin and an inorganic pigment. Examples of inorganic pigments include colored pigments such as titanium oxide, zinc oxide, aluminum oxide, red iron oxide, antimony red, cadmium yellow, cobalt blue, Prussian blue, ultramarine blue, carbon black, and graphite; extender pigments such as silica, calcium carbonate, kaolin, clay, barium sulfate, aluminum hydroxide, and talc; and pearl pigments such as mica and metal oxide-coated mica. These inorganic pigments can be used alone or in combination. Among these, the inorganic pigment preferably contains at least one selected from metal oxides such as titanium oxide, zinc oxide, and aluminum oxide, silica, calcium carbonate, and mica, and more preferably contains titanium oxide.
[0023] The colorant contained in the design print layer is preferably, for example, a pigment, and examples thereof include inorganic pigments and organic pigments used in general inks, paints, recording agents, etc. Examples of organic pigments include soluble azo-based, insoluble azo-based, azo-based, phthalocyanine-based, halogenated phthalocyanine-based, anthraquinone-based, anthanthrone-based, dianthraquinonyl-based, anthrapyrimidine-based, perylene-based, perinone-based, quinacridone-based, thioindigo-based, dioxazine-based, isoindolinone-based, quinophthalone-based, azomethine azo-based, flavanthrone-based, diketopyrrolopyrrole-based, isoindoline-based, indanthrone-based, and carbon black-based pigments. Other examples include carmine 6B, lake red C, permanent red 2B, disazo yellow, pyrazolone orange, carmine FB, cromophtal yellow, cromophtal red, phthalocyanine blue, phthalocyanine green, dioxazine violet, quinacridone magenta, quinacridone red, indanthrone blue, pyrimidine yellow, thioindigo bordeaux, thioindigo magenta, perylene red, perinone orange, isoindolinone yellow, aniline black, diketopyrrolopyrrole red, daylight fluorescent pigments, etc. In addition, both non-acid-treated pigments and acid-treated pigments can be used.
[0024] Whether it is the design printing layer or the second printing layer, the ink (ink composition) that forms the printing layer is composed of a colorant such as the pigment described above, the binder resin described above, the organic solvent described above, and various other additives (such as wax and silica) as necessary.
[0025] The design print layer can be formed by printing an ink containing a binder resin and a colorant using a known printing method. The second printed layer can be formed by printing an ink containing a binder resin and an inorganic pigment using a known printing method. For example, known printing methods include printing with liquid printing inks such as gravure inks and flexographic inks. The thickness of the design print layer is not particularly limited, but is preferably, for example, 0.1 μm to 5 μm, and the thickness of the second print layer is not particularly limited, but is preferably, for example, 0.5 μm to 5 μm.
[0026] In the present invention, when a laminate (printed matter) has multiple ink layers, at least one of the ink layers must be formed using the ink composition of the present invention. Preferably, when a laminate (printed matter) has multiple ink layers, at least the ink layer in contact with the anchor coat layer is formed using the ink composition of the present invention. As shown in the examples below, when the ink layer in contact with the anchor coat layer (in the examples, the color ink layer corresponding to the design print layer) was formed using the ink composition of the present invention, it was found that the laminate showed well-balanced and favorable results in all evaluation items of the physical properties of the overprinted ink print (adhesion, scratch resistance, rubbing resistance, blocking resistance, heat resistance, etc.).
[0027] (Laminate) The laminate of the present invention has an ink layer formed using the ink composition of the present invention. The laminate of the present invention has a heat-shrinkable film and an ink layer, and a more preferred embodiment is a laminate formed by laminating a heat-shrinkable film, an anchor coat layer, and an ink layer in this order.
[0028] <Layer structure of laminate> As described above, the laminate of the present invention is preferably formed by laminating the heat-shrinkable film / anchor coat layer / ink layer in this order. By using the ink composition of the present invention, it is possible to prepare a laminate that can show well-balanced and favorable results in all evaluation items, including pigment dispersibility and various physical properties of overprinted ink prints (adhesion, scratch resistance, crumpling resistance, blocking resistance, heat resistance, etc.). A more preferred embodiment of the laminate of the present invention is, for example, a laminate in which a heat-shrinkable polyolefin film, an anchor coat layer, a design print layer, and a second print layer, a white print layer, are laminated in this order. For example, the anchor coat layer is provided directly in contact with the back surface of the heat-shrinkable polyolefin film, the design printing layer is provided directly in contact with the back surface of the anchor coat layer, and the second printing layer (white printing layer) is provided directly in contact with the back surface of the design printing layer.
[0029] <Heat-shrinkable film> The heat-shrinkable film is preferably a heat-shrinkable polyolefin film. Heat shrinkability refers to the property of shrinking when heated to a required temperature (for example, 70°C to 160°C). A heat shrinkable film heat shrinks in at least one direction (first direction) within its plane, and preferably in two orthogonal directions (first direction and second direction) within its plane.
[0030] The heat-shrinkable polyolefin film is a colorless or colored transparent heat-shrinkable film in which the main component resin constituting the film is a polyolefin-based resin. The heat-shrinkable polyolefin film is not particularly limited, and examples thereof include a polypropylene film made of polypropylene and a polyethylene film made of polyethylene, with a polypropylene film being preferred. Examples of polypropylene include propylene homopolymers and propylene-ethylene copolymers, and examples of polyethylene include polyethylene homopolymers and polyethylene copolymers. The thickness of the heat-shrinkable film is not particularly limited, and is, for example, preferably 10 μm to 60 μm, more preferably 12 μm to 40 μm.
[0031] <Anchor coat layer> The anchor coat layer is disposed between the heat-shrinkable film and the ink layer. The anchor coat layer is formed from an anchor coat layer-forming composition. The anchor coat layer-forming composition contains a binder resin and an organic solvent. The binder resin is not particularly limited and can be appropriately selected depending on the purpose, but it is preferable that the binder resin contains, for example, a chlorinated polyolefin resin. In addition, preferred embodiments of the binder resin in the anchor coat layer-forming composition include, for example, a binder resin containing at least one of a chlorinated polyolefin resin, a rosin-based resin, and a ketone resin.
[0032] <<Binder resin>> As described above, the binder resin in the anchor coat layer-forming composition preferably contains a chlorinated polyolefin resin and at least one of a rosin resin and a ketone resin. More preferred embodiments of the binder resin according to the present invention include binder resins containing chlorinated polyolefin resins, rosin-based resins, and ketone resins.
[0033] The binder resin according to the present invention may further contain at least one resin selected from the group consisting of a cellulose resin, a polyurethane resin, a polyamide resin, an acrylic resin, a polyester resin, and a cyclized rubber. Alternatively, the binder resin according to the present invention may contain, in addition to the chlorinated polyolefin resin and the rosin-based resin or the ketone resin, as a further additional component, at least one resin selected from the group consisting of an alkyd resin, a chlorinated rubber, a butyral, and a petroleum resin, in addition to the cellulose-based resin, the polyurethane resin, the polyamide resin, the acrylic resin, the polyester resin, or the cyclized rubber.
[0034] <<<Chlorinated polyolefin resin>>> The anchor coat layer-forming composition contains a chlorinated polyolefin resin as a binder resin component. The chlorinated polyolefin resin is not particularly limited as long as it is a polyolefin resin in which at least a portion of the hydrogen atoms have been substituted with chlorine atoms. Examples of chlorinated polyolefin resins include chlorinated polyethylene, chlorinated polypropylene, and acrylic-modified or urethane-modified chlorinated polyolefin resins obtained by modifying chlorinated polyethylene or chlorinated polypropylene with an acrylic polymer or urethane polymer having an ethylenically unsaturated bond. The weight average molecular weight of the chlorinated polyolefin resin is preferably 5,000 to 100,000, more preferably 5,000 to 70,000, and even more preferably 7,000 to 50,000. Furthermore, the chlorine content of the chlorinated polyolefin resin is preferably 25 to 45% by mass to improve adhesion to substrates. From the viewpoint of solubility in organic solvents, the chlorine content is more preferably 26 to 43% by mass. Here, the chlorine content refers to the mass % content of chlorine atoms in 100% by mass of the chlorinated polyolefin resin. The chlorinated polyolefin resin is contained in the anchor coat layer forming composition in an amount of preferably 10.0 to 29.0 mass %, more preferably 10.0 to 25.0 mass %, in terms of solid content.
[0035] <<<Rosin-based resin>>> The anchor coat layer-forming composition contains at least one of a rosin resin and a ketone resin as a binder resin component. The rosin-based resin can be any commonly used rosin and / or a commonly used rosin derivative. Specifically, the rosin or rosin derivative is a rosin or a carboxyl group-containing derivative thereof. Examples of the rosin include gum rosin, wood rosin, tall oil rosin, disproportionated rosin, hydrogenated rosin, and polymers thereof. Examples of the rosin derivative include a carboxyl group-containing derivative such as a rosin derivative to which an unsaturated carboxylic acid such as maleic acid, fumaric acid, itaconic acid, or crotonic acid has been added. In the present invention, the rosin-based resin is preferably a rosin-based acid resin. In the present invention, it is particularly preferable to use a rosin-modified maleic acid resin, which is a maleic acid derivative of rosin, or a rosin-modified fumaric acid resin, which is a fumaric acid derivative of rosin. The rosin-modified maleic acid resin or rosin-modified fumaric acid resin used in the present invention is not particularly limited, and any known rosin-modified maleic acid resin or rosin-modified fumaric acid resin can be used. The rosin-modified maleic acid resin or rosin-modified fumaric acid resin preferably has an acid value of 25 mgKOH / g or more and 320 mgKOH / g or less, and particularly preferably has an acid value of 100 mgKOH / g or more and 320 mgKOH / g or less. As the rosin-based acid resin, for example, the Marquid series manufactured by Arakawa Chemical Industries, Ltd. can be used.
[0036] <<<Ketone resin>>> The anchor coat layer-forming composition contains at least one of the above-mentioned rosin-based resin and ketone resin as a binder resin component. The ketone resin according to the present invention is as described above in the description of the "ketone resin" in the "binder resin" in the "ink composition" section.
[0037] At least one of the rosin resin and the ketone resin is contained in the anchor coat layer forming composition in an amount of preferably 10.0 to 40.0 mass %, more preferably 15.0 to 35.0 mass %. When both a rosin resin and a ketone resin are contained, the above-mentioned preferable content range is the total content of both resins. When the binder resin in the anchor coat layer-forming composition contains a chlorinated polyolefin resin, a rosin-based resin, and a ketone resin, the content ratio of the chlorinated polyolefin resin, the rosin-based resin, and the ketone resin is preferably 60.0-80.0:15.0-35.0:1.0-10.0 by mass.
[0038] <<Organic solvents>> The organic solvent according to the present invention is as described above in the description of the <organic solvent> in the (ink composition) above.
[0039] The anchor coat layer-forming composition of the present invention may further contain at least one of wax and silica.
[0040] <<Wax>> The anchor coat layer forming composition may contain a wax. As the wax, it is preferable to use, for example, the polyolefin wax or fatty acid amide wax described in the description of the wax in the above (Ink composition).
[0041] The wax is contained in the anchor coat layer forming composition in an amount of preferably 0.1 to 5.0% by mass, and more preferably 0.5 to 2.5% by mass. The content of silica in the anchor coat layer forming composition is preferably 0.1 to 5.0 mass %, and more preferably 0.5 to 2.5 mass %.
[0042] The anchor coat layer can be formed by applying the anchor coat layer-forming composition of the present invention to a substrate such as a heat shrinkable film, and drying the coating film. The thickness of the anchor coat layer is not particularly limited, but is preferably 0.01 μm to 3 μm, and more preferably 0.05 μm to 2 μm, for example.
[0043] <Preferred embodiment of ink layer in laminate> A preferred embodiment of the laminate including an ink layer is, for example, the following embodiment (i). (i) Heat-shrinkable film / solvent (oil-based) anchor coat layer / solvent (oil-based) ink layer
[0044] <Method of manufacturing laminate> The laminate of the present invention can be produced, for example, as follows. The anchor coat layer-forming composition is applied to a heat-shrinkable film substrate, and the coating film is dried to form the anchor coat layer. An ink (ink composition) is applied onto the anchor coat layer, and the coating film is dried to form an ink layer. Furthermore, by changing the type of ink, multiple ink layers (printed layers) can be formed in sequence, from the first ink layer (first printed layer) to the second ink layer (second printed layer), and then, as appropriate, the third ink layer (third printed layer), the fourth ink layer (fourth printed layer), etc.
[0045] <Application of laminates> The laminate of the present invention is used, for example, as an overwrap film for overwrap packaging, particularly for packaging cup noodles. The overlap film according to the present invention is used by being attached to various adherends by heat shrinking. An overlap film is used as a protective film by wrapping it around a single adherend, or as a protective and bundling film by wrapping it around an assembly of multiple adherends. The adherend is not particularly limited, and may be a container in which an article is stored, or the article itself. Examples of the substrate include containers containing instant foods such as instant noodles, dairy products such as yogurt, luxury foods such as jellies and puddings, beverages, seasonings, sanitary products such as shampoo, and fresh foods such as meat; and articles themselves such as dry batteries. When the adherend is a container containing an article, the external shape of the container is not particularly limited, and examples thereof include cylindrical shapes such as a cylindrical, elliptical, or rectangular cylinder; inverted truncated cone shapes such as an inverted truncated elliptical cone shape or an inverted truncated square pyramid; and irregular shapes such as a gourd shape. The material of the container is not particularly limited, and examples thereof include synthetic resin, foamed synthetic resin, metal, glass, ceramic, and wood.
[0046] <<Specific uses of overlap film>> In mechanical manufacturing processes, packages in which an adherend is wrapped in overlap film are usually produced as follows: For example, a long overlap film is formed into a cylindrical shape so as to wrap around the adherend, and both side edges along the MD (longitudinal direction) are heat-sealed, and the long overlap film formed into a cylindrical shape wrapping the adherend is thermally sealed in the TD on both the front and rear sides of the adherend, and then the overlap film, sealed on three sides with the adherend inside, is heated to heat shrink the package, thereby obtaining a package. [Example]
[0047] The present invention will be described in more detail below using examples. Of course, the present invention should not be limited to the scope of these examples. Hereinafter, "parts" and "%" are by mass unless otherwise specified.
[0048] (Preparation of various compositions) As a composition for forming an anchor coat layer, an oil-based anchor coat varnish of Preparation Example-AC1 shown in Table 1 below was prepared. As the inks, oil-based color inks of Preparation Example - Color 1, Preparation Example - Comparative Color 1 to Preparation Example - Comparative Color 4 shown in Table 2 below were prepared. As the ink, oil-based white inks of Preparation Example White 1, Preparation Example Comparative White 1 to Preparation Example Comparative White 4 shown in Table 3 below were prepared.
[0049] [Table 1]
[0050] The raw materials used in the table are as follows: Chlorinated polypropylene resin: Nippon Paper Industries Co., Ltd. "Super Chlon 360T, 60% solids" Rosin-modified maleic acid resin: Arakawa Chemical Industries, Ltd. "Marquid No. 31" Ketone formaldehyde resin: Commercially available 100% solid ketone formaldehyde resin Cyclized rubber: Commercially available cyclized rubber with 100% solids content Silica: Fuji Silysia Chemical "Sylysia 436"
[0051] <Preparation Example - AC1> 14.1 parts of chlorinated polyolefin resin solid content, 4.7 parts of rosin-modified maleic acid resin solid content, 0.9 parts of ketone formaldehyde resin solid content, 1.1 parts of cyclized rubber solid content, 37.7 parts of methylcyclohexane, 19.0 parts of normal propyl acetate, 11.5 parts of normal propyl alcohol, and 1.5 parts of silica were stirred to prepare Preparation Example-AC1.
[0052] [Table 2] The raw materials used in the table are as follows: Carbon black: Orion Engineered Carbons "Special Black 250 Powder" Nitrocellulose resin: NOBEL "NITROCELLULOSE DHX3-5" Polyamide resin: Commercially available 100% solid polyamide resin Ketone formaldehyde resin: Commercially available 100% solid ketone formaldehyde resin Urethane resin: DIC "Burnoch ECL-341" Acrylic resin: Taisei Fine Chemical Co., Ltd. "Acrit Series" Silica: Fuji Silysia Chemical "Sylysia 436"
[0053] <Preparation Example - Color 1> 15.0 parts of carbon black, 8.1 parts of soluble nitrocellulose resin, 6.1 parts of solid polyamide resin, 2.4 parts of solid ketone formaldehyde resin, 41.3 parts of normal propyl alcohol, and 26.1 parts of normal propyl acetate were mixed and kneaded, and 1.0 part of silica was added to produce Preparation Example - Color 1.
[0054] <Preparation example-ratio color 1> 15.0 parts of carbon black, 14.2 parts of nitrocellulose resin solids, 2.4 parts of ketone formaldehyde resin solids, 41.3 parts of normal propyl alcohol, and 26.1 parts of normal propyl acetate were mixed and kneaded, and 1.0 part of silica was added to prepare Preparation Example - Comparative Color 1.
[0055] <Preparation example-ratio color 2> 15.0 parts of carbon black, 14.2 parts of solid polyamide resin, 2.4 parts of solid ketone formaldehyde resin, 41.3 parts of normal propyl alcohol, and 26.1 parts of normal propyl acetate were mixed and kneaded, and 1.0 part of silica was added to prepare Preparation Example - Comparative Color 2.
[0056] <Preparation example-ratio color 3> 15.0 parts of carbon black, 16.5 parts of urethane resin solids, 41.3 parts of normal propyl alcohol, and 26.1 parts of normal propyl acetate were mixed and kneaded, and 1.0 part of silica was added to prepare Preparation Example - Comparative Color 3.
[0057] <Preparation example-ratio color 4> 15.0 parts of carbon black, 8.1 parts of soluble nitrocellulose resin, 8.5 parts of solid polyamide resin, 41.3 parts of normal propyl alcohol, and 26.1 parts of normal propyl acetate were mixed and kneaded, and 1.0 part of silica was added to prepare Preparation Example - Comparative Color 4.
[0058] [Table 3]
[0059] In the table, the following raw materials were used: Titanium oxide: Teika "TITANIX JR-808" Polyamide resin: Commercially available 100% solid polyamide resin Ketone formaldehyde resin: Commercially available 100% solid ketone formaldehyde resin Nitrocellulose resin: NOBEL "NITROCELLULOSE DHX3-5" Urethane resin: DIC "Burnoch ECL-341" Silica: Fuji Silysia Chemical "Sylysia 436" Paraffin wax: Accumelt 8756A manufactured by THE INTERNATIONAL GR
[0060] <Preparation example-white 1> 51.8 parts of titanium oxide, 6.8 parts of polyamide resin solids, 3.3 parts of ketone formaldehyde resin solids, 2.0 parts of nitrocellulose resin solids, 21.2 parts of normal propyl alcohol, 5.8 parts of methylcyclohexane, and 5.0 parts of normal propyl acetate were mixed and kneaded, and 2.5 parts of silica and 1.5 parts of paraffin wax were added to produce Preparation Example - White 1.
[0061] <Preparation example - Hiraku 1> 51.8 parts of titanium oxide, 3.3 parts of ketone formaldehyde resin solids, 8.8 parts of nitrocellulose resin solids, 21.2 parts of normal propyl alcohol, 5.8 parts of methylcyclohexane, and 5.0 parts of normal propyl acetate were mixed and kneaded, and 2.5 parts of silica and 1.5 parts of paraffin wax were added to produce Preparation Example - White 1.
[0062] <Preparation example - Hiraku 2> 51.8 parts of titanium oxide, 8.8 parts of solid polyamide resin, 3.3 parts of solid ketone formaldehyde resin, 21.2 parts of normal propyl alcohol, 5.8 parts of methylcyclohexane, and 5.0 parts of normal propyl acetate were mixed and kneaded, and 2.5 parts of silica and 1.5 parts of paraffin wax were added to produce Preparation Example - White 2.
[0063] <Preparation example - Hiraku 3> 51.8 parts of titanium oxide, 12.1 parts of urethane resin solids, 21.2 parts of normal propyl alcohol, 5.8 parts of methylcyclohexane, and 5.0 parts of normal propyl acetate were mixed and kneaded, and 2.5 parts of silica and 1.5 parts of paraffin wax were added to produce Preparation Example - White 3.
[0064] <Preparation example - Hiraku 4> 51.8 parts of titanium oxide, 6.8 parts of polyamide resin solids, 5.3 parts of nitrocellulose resin solids, 21.2 parts of normal propyl alcohol, 5.8 parts of methylcyclohexane, and 5.0 parts of normal propyl acetate were mixed and kneaded, and 2.5 parts of silica and 1.5 parts of paraffin wax were added to produce Preparation Example 4.
[0065] (Printing method) The oil-based anchor coat varnish described in Preparation Example was prepared with methylcyclohexane in a Zahn Cup #4 (manufactured by Rigo Co., Ltd.) for 10 seconds (25°C). The inks (oil-based color inks, oil-based white inks) described in the Preparation Examples were each prepared with a 50 / 50 mixed organic solvent of normal propyl acetate / n-propyl alcohol in a Zahn Cup #4 (manufactured by Rigo Co., Ltd.) for 10 seconds (25°C). Using a Windmill CI-type 6-color flexographic printing machine SOLOFLEX, various oil-based anchor coat varnishes or inks were printed onto a biaxially oriented polypropylene film (thickness 15 μm) substrate to obtain laminates (printing ink laminates) with the configurations shown in Table 4 below. The printing order of the oil-based anchor coat varnish and ink was as shown in Table 4, with the anchor coat layer (first printed layer), color ink layer (second printed layer), and white ink layer (third printed layer) printed in that order.
[0066] The laminates (printing ink laminates) prepared in Table 4 were subjected to the following evaluations.
[0067] (Evaluation of laminate) [Pigment dispersibility] The pigment dispersibility of the prepared ink composition was visually evaluated using a grind meter M100 (manufactured by Toyo Seiki Co., Ltd.). -Evaluation criteria- 3. No coarse pigment particles and uniform 2. Fewer coarse pigment particles 1 Coarse pigment particles are visible
[0068] [Printability (ink transfer)] When the inks were printed using the method described in the above (Printing Method) section, the transferability of various color and white inks onto the anchor coat layer was evaluated visually. -Evaluation criteria- 4. No ink transfer problems observed 3. Poor ink transfer is hardly observed. 2. Slight ink transfer failure is observed. 1 Poor ink transfer is evident
[0069] [Adhesion before shrinkage] After printing the anchor coat layer and the ink layer, cellophane tape (manufactured by Nichiban Co., Ltd.) was applied to the printed surface, and then the tape was quickly peeled off, and the condition of the printed surface was evaluated visually. -Evaluation criteria- 4 The printed film does not peel off at all from the film 3 Less than 30% of the printed film surface area peels off from the film. 2. The area ratio of the printed film is 30% or more but less than 70% and peels off from the film. 1 At least 70% of the printed surface area is peeled off from the film.
[0070] [Scratch resistance before shrinkage] The ink layer surface of the resulting laminate (printed material) was rubbed back and forth with a fingernail 20 times, and the state of removal of the film from the printed surface was visually evaluated. -Evaluation criteria- 4. The printed film does not peel off from the film substrate at all. 3 Less than 30% of the printed film surface area peels off from the film substrate. 2. The area ratio of the printed film is 30% or more but less than 70% and peels off from the film. 1 70% or more of the printed surface area is peeled off from the film substrate.
[0071] [Crush resistance before shrinkage] The ink layer surfaces of the resulting laminate (printed matter) are rubbed back and forth five times to of the membrane The state of the catch was evaluated visually. -Evaluation criteria- 4. The printed film does not peel off from the film substrate at all. 3 Less than 30% of the printed film surface area peels off from the film substrate. 2. The area ratio of the printed film is 30% or more but less than 70% and peels off from the film. 1 70% or more of the printed surface area is peeled off from the film substrate.
[0072] [Adhesion after shrinkage] The resulting laminate (printed material) was shrunk in a thermostatic chamber at 120° C. for 30 seconds. Next, cellophane tape (manufactured by Nichiban Co., Ltd.) was applied to the printed surface, and the tape was quickly peeled off, and the condition of the printed surface was visually evaluated. -Evaluation criteria- 4. The printed film does not peel off from the film substrate at all. 3 Less than 30% of the printed film surface area peels off from the film substrate. 2. The area ratio of the printed film is 30% or more but less than 70% and peels off from the film. 1 70% or more of the printed film surface area peels off from the film substrate.
[0073] [Blocking resistance] The ink layer surface of the prepared laminate (printed material) was placed against the film substrate, and left for one day in a blocking tester under conditions of pressure: 0.5 MPa, temperature: 40°C, and humidity: 80%. After the test, the peeling properties and condition of the surface were evaluated. -Evaluation criteria- 4 When peeling the printed surfaces apart, there is no resistance and there are no particular problems with the surface. 3 When peeling the printed surfaces apart, there is some resistance and the surfaces are slightly stuck together. 2 When peeling the printed surfaces apart, there is resistance, but the ink layer does not peel off. 1 When peeling the printed surfaces apart, there is considerable resistance and the ink layer is peeling off.
[0074] [Heat resistance] The ink layer surface of the prepared laminate (printed material) is placed against a polystyrene sheet that represents the container in which the printed surface will be accumulated, and the sheets are pressed together with a heat seal bar at a pressure of 0.1 MPa for 1 second, and the extent to which the film on the printed surface has been removed is checked. Test temperature: 120℃ -Evaluation criteria- 4. The printed film does not come off at all on the polystyrene sheet. 3. The printed film is less than 30% of the surface area of the polystyrene sheet. 2. The printed film covers less than 50% of the surface area of the polystyrene sheet. 1. The printed film covers 70% or more of the surface area of the polystyrene sheet.
[0075] (Examples 1 to 3, Comparative Examples 1 to 4) The evaluation results for the laminates (printed materials) of the examples and comparative examples shown in Table 4 below are also shown in the same Table 4.
[0076] [Table 4]
[0077] From the results of Examples 1 to 3 and Comparative Examples 1 to 4, it was found that laminates (printed matter) having ink layers formed using the ink composition of the present invention are laminates that can show well-balanced and favorable results in all evaluation items, including pigment dispersibility and various physical properties of overprinted ink prints (adhesion, scratch resistance, crumpling resistance, blocking resistance, heat resistance, etc.). In Table 4, if the evaluation score is 3 or higher, the laminate can be used practically. In this respect, Comparative Examples 1 to 4, which were formed using ink compositions that do not satisfy the requirements of the present invention, did not provide sufficient evaluation results. Furthermore, when multiple ink layers are formed in a laminate (printed matter), it has been confirmed that if the ink layer in contact with the anchor coat layer (in the examples, the color ink layer corresponding to the design printing layer) is formed using the ink composition of the present invention, a laminate can be obtained that can show balanced and good results in all evaluation items of the physical properties of the overprinted ink printed matter (adhesion, scratch resistance, rubbing resistance, blocking resistance, heat resistance, etc.) (see the comparison results between Example 1 and Examples 2-3).
Claims
1. Contains a binder resin and an organic solvent, The ink composition, wherein the binder resin contains soluble nitrocellulose resin, polyamide resin, and ketone resin.
2. The ink composition according to claim 1, wherein the soluble nitrocellulose resin and the polyamide resin are contained in an amount of 60 mass % or more in terms of solid content relative to the total amount of the binder resin.
3. The ink composition according to claim 1 , wherein the organic solvent contains at least one of an aliphatic hydrocarbon solvent, an ester solvent, an alcohol solvent, and a glycol ether solvent.
4. The ink composition according to claim 1 , further comprising at least one of a wax and silica.
5. The ink composition according to claim 1, which is used to form an ink layer in a laminate having a heat-shrinkable film and an ink layer.
6. A laminate comprising a heat-shrinkable film, an anchor coat layer, and an ink layer laminated in this order, A laminate, wherein the ink layer is a layer formed using the ink composition according to any one of claims 1 to 5.
7. The laminate according to claim 6 , wherein the heat shrinkable film is a polyolefin film.
8. A laminate comprising a heat-shrinkable film, an anchor coat layer, and an ink layer laminated in this order, The laminate according to claim 6, wherein the ink layer comprises two or more ink layers, and of the two or more ink layers, at least the ink layer in contact with the anchor coat layer is a layer formed using the ink composition according to any one of claims 1 to 5.
9. A laminate comprising a heat-shrinkable film, an anchor coat layer, and an ink layer laminated in this order, The laminate according to claim 6, wherein the ink layer comprises two or more ink layers, and each of the two or more ink layers is a layer formed using the ink composition according to any one of claims 1 to 5.
10. The laminate according to claim 6 , wherein the anchor coat layer-forming composition that forms the anchor coat layer contains at least a chlorinated polyolefin resin as a binder resin.
Citation Information
Patent Citations
Overlapping film, and packaging body
JP2016141403A